Pullulanase Debranching of Various Starches Upgrades the Crystalline Structure and Thermostability of Starch‐Lauric Acid Complexes - Wongprayoon, Suchitra; Tran, Thierry; Gibert, Olivier; Dubreucq, Eric; Piyachomkwan, Kuakoon; Sriroth, Klanarong (Wiley, 2018)
Cassava, rice, and chickpea starches with different amylose contents and amylopectin structure are used to prepare helical inclusion complexes with lauric acid (LA) and to investigate the effect of pullulanase debranching on complex formation, crystalline structure, thermostability, and morphology compared to their non‐debranched counterparts. The quantity of inclusion complexes in debranched starches increased 2–9 times compared to non‐debranched starches, due to the release of debranched, linear amylopectin chains. The amount of complexes after debranching increased with amylopectin content, and with the proportion of amylopectin short chains. Retrogradation occurred under the same conditions as and in competition with complexation; however, carefully adjusting the conditions enabled minimization of retrogradation and maximization of complex formation.